2014
DOI: 10.1186/ar4442
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of blood B-cell subset profiling and autoimmunity markers in Sjögren’s syndrome

Abstract: IntroductionThe aims of this study were to evaluate the diagnostic accuracy of blood B-cell subset profiling and immune-system activation marker assays in primary Sjögren’s syndrome (pSS) and to assess whether adding these tools to the current laboratory item would improve the American-European Consensus Group (AECG) criteria.MethodsIn a single-center cohort of patients with suspected pSS, we tested the diagnostic performance of anti-SSA, antinuclear antibody (ANA), rheumatoid factor (RF), gammaglobulins, IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 18 publications
(28 reference statements)
3
16
1
1
Order By: Relevance
“…The immune cells from patients with pSS are activated in vivo, as demonstrated by increased expression of activation markers in T and B cells and secretion of autoantibodies by B cells [1,[23][24][25]. This activated phenotype might increase sensitivity to cytokine signaling.…”
Section: Discussionmentioning
confidence: 96%
“…The immune cells from patients with pSS are activated in vivo, as demonstrated by increased expression of activation markers in T and B cells and secretion of autoantibodies by B cells [1,[23][24][25]. This activated phenotype might increase sensitivity to cytokine signaling.…”
Section: Discussionmentioning
confidence: 96%
“…Antinuclear antibodies positivity was defined in our cohort as a 1:320 titer or higher to exclude low titer ANA positivity as it’s not so specific especially in older people or those with other chronic diseases. Further, it is suggested that ANA 1:320 positivity and RF (especially IgA type of RF) are both related to the presence of anti‐SSA antibodies, and ANA 1:640 positivity and blood B‐cell subset profiling have good diagnostic properties for pSS . Therefore, high titer ANA positivity is much more significant in pSS.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, anti-SSA/SSB antibodies are the most specific markers, but are present in only 50% to 75% of pSS diagnostics. The anti-nuclear antibodies present in 80% of pSS and the rheumatoid factors in 40% to 75% of pSS, are non specific and can be found in other systemic autoimmune diseases [3][4][5]. The Sjögren's Syndrome is considered secondary (sSS) when associated with other connective tissue disease.…”
Section: Accepted Manuscriptmentioning
confidence: 99%